Avaliação da fibra de coco (mesocarpo do fruto de Cocos nucifera L.) como adsorvente para remoção do agrotóxico parationa metílica de meio aquoso - (:unkn) unknown (Universidade Federal de Goiás, 2017)
In this work, experiments were performed to study the potential of coconut fiber (Cocos nucifera L.) as adsorbent for removing the pesticide parathion methyl from water. The analytical methodology used to quantify the pesticide in the adsorption studies was based on solid phase extraction (SPE) and gas chromatography with electron capture detection (GC/ECD). The method were validated and showed good analytical features in terms of selectivity, linearity, accuracy (recovery: 100.4%), precision (coefficient of variation: 9.63%;), limit of detection (0.003 mg L-1 ) and quantification (0.010 mg L-1 ). The matrix effect in pesticide quantification was evaluated and the results showed an enhanced chromatographic response for the parathion methyl in all the concentrations evaluated due to interference of endogenous coconut fiber compounds present in the solution after adsorption tests, therefore, the quantification was made using matrix-standard calibration solutions to compensate for matrix-induced effects and to obtain more accurate results. The adsorbent characterization (FTIR, MEV, surface area and pHpcz) showed that coconut fiber surface is composed of very irregular particles, with many cavities (pore diameter: 3.48 nm) and external surface area of 3.64 m2 g -1 . The presence of several functional groups: carboxylate, hydroxyl, carboxyl, among others was observed. The pH at point of zero charge (pHpcz) for the adsorbent was 5.85. The adsorption capacity of the coconut fiber was evaluated under different parameters: adsorbent treatment, adsorbent dosage, contact time and concentration of the pesticide. The adsorbent treatment with water, HCl or NaOH did not affect the adsorption capacity (75.6% of removal was obtained, independently of the treatment). The increasing in the adsorbent dosage of 5 to 20 g L-1 caused an increasing in the adsorption capacity from 25.0% to 76.6%. The adsorption equilibrium process was reached after 90 minutes of contact, with 86.1% of removal. The kinetic study showed that the Avrami kinetic model was the best fit for the experimental data. The adsorption capacity improved as function of the pesticide concentration increasing. The experimental data were fitted to Langmuir, Freundlich and Sips isotherm models and the best fit was obtained with Freundlich and Sips models. The maximum adsorption capacity (Qmax) were 39.8547 mg g-1 . Additional tests showed that the adsorption capacity was slightly affected when using real samples (natural water) in the adsorption experiments (82.24% removal) and presented excellent adsorption capacity when used in an alternative column adsorption procedure (85.73% removal). The results indicate that the coconut fiber has a great potential to be used as adsorbent material for the treatment of water contaminated with the pesticide methyl parathion.
Evaluation of coconut fiber (Cocos nucifera L.) as adsorbent for removing the pesticide parathion methyl from water
Keywords: Fibra de coco; Adsorvente; Parationa metílica; Extração em fase sólida; Efeito de matriz; Cromatografia gasosa; Coconut fiber; Adsorbent; Methyl parathion; Solid phase extraction; Matrix effect; Gas chromatography; CIENCIAS EXATAS E DA TERRA::QUIMICA